The validity and practicality of the SEDC learning model in enhance student’s higher order thinking skills in science learning - Rusmala Evi Anggraeni; S Suratno; Erlia Narulita (Biosfer: Jurnal Pendidikan Biologi, 2022)
As we move into the twenty-first century, education is becoming increasingly critical in order to ensure that every student has the skills necessary to meet the demands of the twenty-first century. The challenge in the world of education in Indonesia today is to provide quality education that is capable of producing competent human resources. To meet the demands of the twenty-first century, STEM-based education is required. Students in Era 4.0 must not only have high-order thinking skills, but also digital literacy. Teachers and students must be able to make the best use of technology, which would enable teachers to develop an online learning setting. The effects of the Covid-19 pandemic have hastened the adoption of information technology in the field of education. By use of digital learning during COVID-19 offered excellent opportunities for teachers to gain experience in digital learning and teaching. The teacher must first plan by using a learning model that supports the online learning process, such as the Community of Inquiry (CoI). Therefore, the development of a STEM-based CoI learning model was carried out, namely SEDC. The aim of this study is to assess the SEDC learning model's validity and practicality. This study uses a 4D design to define, design, develop, and disseminate. In this study, 116 students participated in small-scale test, large-scale test, and dissemination studies, with two expert lecturers as validators and one teacher as users. The validation results were 95.6% with very valid categories, according to the findings. The result for practicality is 84.69% in the very practical category. As a result, this learning model can be concluded to be both valid and useful in rising HOTS. Therefore, it's suggested that it's used in the learning process